School leadership - Ravit, Amir (IJRDO - Journal of Applied Management Science, 2016)
In today’s world we are engaged in endless preparation of lists of almost everything we know. We already lists of the richest people in the world, the most numerous downloads from the Internet, the most beloved movies, a thousand and one things that must be enough to do, see or visit during life, and so on and so on! Education is no different - there are lists of characteristics of effective schools, effective teachers, six ways to manage the behavior of students, the ten main lessons learned regarding school .improvement and the key characteristics of school leaders successful Indeed, often these lists are useful summaries of knowledge at our disposal, but should be treated with caution Hrsimti logic, "as Roland Barthes called" the way of thinking 20 years ago (Barth 1990: 38). This is, in part, because such lists can be used nucleic While thinking, but not all provide us with sufficient illumination or deepening our knowledge as we would like. Otherwise, today there are already so many lists on education and !leadership to the need for preparation of a list of lists Society for Research on education (American Educational Research Association), for example, invited a team of researchers form the totality of what we know about school leadership success (Leithwood & Riehl, 2003). The result Lotsh and was developed further and become known as Seven strong claims about the verification test school leadership ("Seven convincing case about school leadership succeeds in" Leithwood et al. 2006). Around the same time the value of the National Institute for School Leadership (NCSL), England synthesis of all the research on leadership committed five years of active research and knowledge production. The Institute gathered together commissioned research findings, studies of the area and the conclusions derived seminars and think tanks, and produced an overview of recent knowledge on the subject of school leadership.